Peningkatan Hasil Belajar Siswa melalui Educaplay pada Materi “Tanda Seru” Kelas 2 SD Negeri Plaosan - Azizah, Athifah Nur; Ayuni, Meita Nur (MASALIQ, 2025)
This study analyzes the improvement of student learning outcomes with the help of educaplay edugame on the material “Exclamation Mark” grade 2 SD N Plaosan. This study aims to determine the application of Educaplay digital edugame on the material “Exclamation Mark” in grade 2 SD Negeri Plaosan and to determine student learning outcomes through educaplay digital edugame on the material “Exclamation Mark” in grade 2 SD Negeri Plaosan. The method used is Classroom Action Research (PTK) involving 15 grade 2 students as samples. The data instrument techniques used were observation, interview, questionnaire, and test. Data were collected using pretest and postest. The results showed that: (1) the learning process with the help of educaplay runs according to the lesson plan, (2) there is an increase in student learning outcomes through pretest and posttest, (3) student learning outcomes through educaplay increased from initially 40% of the number of students completed to 86.6% of students completed in Indonesian language subjects (4) the application of educaplay edugame is considered effective to improve the learning outcomes of grade 2 students in Indonesian language subjects.